POLA PENGGUNAAN INSTAGRAM DI KALANGAN SISWA SISWI KELAS XI SMA NEGERI 7 KOTA MEDAN - Jannatun Nisa; Billqis Efriza Lubis (MESSAGE: JURNAL KOMUNIKASI, 2020)
The current digital era has succeeded in changing the community culture of the world from traditional to modern conditions. Social media becomes inseparable for human life including among students SMA Negeri 7 Medan. So it’s interesting to do a study quantitative descriptive. This study aims at finding out patterns or motives for using Instagram among students of SMA Negeri 7 Medan and the frequency of accessing Instagram.The theories that are considered relevant in this study are theories: Uses Gratification. The population in this study are students of SMA Negeri 7 Medan. Determination of the sample using the Slovin formula with a precision of 10% and a confidence level of 90% to obtain a sample of 71 people. The sampling technique uses purposive sampling with criteria, namely; grade XI students of SMA Negeri 7 Medan, have an Instagram account, and actively use the Instagram account. Data collection was carried out through field research using questionnaires and literature studies. Data analysis was performed through a single table analysis using the SPSS 24 program, then analyzed and interpreted. The results of the study: The use of Instagram among grade XI students of SMA Negeri 7 Medan is as follows: The intensity of Instagram users is active users who are still using it, the frequency of use ranges from 1-2 hours during the day, the motives used in choosing Instagram are information, personal identity, integrity, social interaction and entertainment. One of the benefits that can be felt is getting the latest information, adding insight, building relationships, Almost all students feel benefits in terms of information and entertainment via Instagram.